Effective government accounting - Premchand, A. (Washington, D.C. : International Monetary Fund, 1995)
This book, the first of its type, seeks to bridge fiscal economics and government accounting. For too long government accounting has been neglected, and governments have not developed the institutional capacity to formulate and implement fiscal policies successfully. This volume examines historical developments, ingredients and existing systems features of accounting standards, and other issues that governments must address to perform their tasks economically and efficiently. It explores institutional linkages and the role of electronic processing technology. Arguing that government accounting systems are too important to be left to accountants alone, the book presents an interdisciplinary approach that goes beyond adapting commercial accounting formats to governments.
Includes bibliographical references (p. 186-190).
opc 27/09/16
Loans
Keywords: Finance, Public - Accounting; Accounting - Government